Inovasi Pembelajaran Berbasis Kotak Pada Anak Usia Dini - Muhammad Rusydu; Satriani Junaid; Hartina (Prodi PIAUD STAI AL-GAZALI BONE, 2026)
This study aims to describe the implementation of box-based learning innovation in early childhood education, focusing on the learning process, children’s learning experiences, and the role of teachers in creating active and enjoyable learning activities. The study employed a qualitative descriptive approach conducted in early childhood education institutions implementing box-based learning media. Data were collected through participatory observation, semi-structured interviews, and documentation, while thematic analysis was used to identify patterns related to learning activities, children’s responses, and teacher strategies. The findings reveal that box-based learning media create interactive and meaningful learning experiences by encouraging children to explore, classify, arrange, and communicate through play activities. The use of concrete and multisensory media positively contributes to children’s cognitive, language, motor, social-emotional, and creative development. Children showed greater enthusiasm, concentration, participation, and communication skills during the learning process. Teachers also played an important role as facilitators in designing contextual and child-centered learning activities. Despite several challenges, such as limited preparation time and learning media availability, box-based learning innovation is considered effective in supporting enjoyable, inclusive, and developmentally appropriate learning for early childhood education.